Hybrid Model for Production Plan - Ali, A. J. Adham (LAP LAMBERT Academic Publishing, 2014)
Automobile manufacturing is one of the most important industries in the world. The Production Line Plan (PLP) is one of the main supply chain of this industry. In this book The Hybrid Model (HM) used a new method to solve the PLP problem. The HM is involving the Simulation Model (SM), Multi-Objectives Model (MOM), and Genetic Algorithm (GA) system. Furthermore, the Simulation Model (SM) is used to solve the PLP problem to achieve the customer order by increasing the quantity of production. The new approach is called Hybrid Model of the Production Line Plan (HMPLP). This approach is employed to solve the production line problems and to develop the efficiency of the production line. As a result, the Hybrid Model is developed to solve the Production Line System (PLS), by applying to solve the PLP to make a new plan, then to make several strategies to solve the PLP problem and to achieve the customer orders. The aim of this study is to combine Mixed Model (MOM and GA) with SM to develop the efficiency of the production line and to solve PLP problem. This is a new method to obtain the best or the optimum balance between the quantity of customers demand and the production quantity. The method increased the ratio of the production and the production plan profit.